Assessment of urea hydrolysis as a pretreatment strategy to improve total nitrogen rejection from urine using aquaporin-based membranes in forward osmosis. (April 2020) - Engelhardt, Sebastian; Vogel, Jörg; Duirk, Stephen E.; Moore, Francisco B.; Barton, Hazel A.
Abstract: Energy-efficient technologies that allow for the effective recovery of water from urine are desirable in a variety of environments. While light-weight and portable forward osmosis (FO) systems have many advantages over other energy-intensive approaches, they often do not achieve a high water recovery, while small and uncharged solutes such as urea are efficiently rejected by the FO membrane. Hollow fiber aquaporin-based membranes (ABMs) represent potential candidates to be used in urine filtration and past work has demonstrated that charged ammonium ions are rejected more efficiently than uncharged urea at low pH. In this study, we examined urea hydrolysis via the enzyme urease as a pre-FO treatment strategy to see if rejection of nitrogenous compounds can be enhanced. Our results demonstrate that urea hydrolysis in combination with lowering the feed solution pH significantly improved total nitrogen (TN) rejection. Nonetheless, the increased osmolarity of the resulting feed solution compromised water recovery, which was especially noticeable when glucose draw solutions were utilized. Therefore, our results suggest that the introduced strategy is not practicable for general field application. However, the introduced approach may still be beneficial in applications where draw solutions of high osmolarity can be used to allow for an efficient water recovery from urine.